Cry1 and GPA1 signaling genetically interact in hook opening and anthocyanin synthesis in Arabidopsis - Fox, Ana Romina (2012)
While studying blue light-independent effects of cryptochrome 1 (cry1) photoreceptor, we observed premature opening of the hook in cry1 mutants grown in complete darkness, a phenotype that resembles the one described for the heterotrimeric G-protein α subunit (GPA1) null mutant gpa1. Both cry1 and gpa1 also showed reduced accumulation of anthocyanin under blue light. These convergent gpa1 and cry1 phenotypes required the presence of sucrose in the growth media and were not additive in the cry1gpa1 double mutant, suggesting context-dependent signaling convergence between cry1 and GPA1 signaling pathways. Both, gpa1 and cry1 mutants showed reduced GTP-binding activity. The cry1 mutant showed wild-type levels of GPA1 mRNA or GPA1 protein. However, an anti-transducin antibody (AS/7) typically used for plant Gα proteins, recognized a 54 kDa band in the wild type but not in gpa1 and cry1 mutants. We propose a model where cry1-mediated post-translational modification of GPA1 alters its GTP-binding activity. © 2012 Springer Science+Business Media B.V.